2015
DOI: 10.3892/mmr.2015.3949
|View full text |Cite
|
Sign up to set email alerts
|

Soy isoflavones protect against H2O2-induced injury in human umbilical vein endothelial cells

Abstract: The aim of this study was to investigate the effects of soy isoflavones on the injury of human umbilical vein endothelial cells induced by H2O2. EVC‑304 cells were preincubated with soy isoflavones for 12 h, and then exposed to 100 µM H2O2 for 1 h. Cell viability was evaluated by a 3‑(4,5‑di‑methylthiazol‑2‑yl) 2,5‑diphenyltetrazolium bromide assay. The apoptosis of EVC‑304 cells was detected by Hoechst 33258 and Annexin‑V/propidium iodide staining. The oxidative stress‑related biochemical parameters were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…In our trial, in ovo injection of different doses of ISF increased GSH-PX activity in the serum of chicks (Hajati et al, 2014;Khaligh et al, 2018). Furthermore, in vitro studies in human and pig cells challenged by hydrogen peroxide showed that ISF increased the activities and mRNA expression of SOD and GSH (Jin et al, 2015;Khaligh et al, 2018;Ma et al, 2015). In the current study, no change was observed in Ca, P, albumen, TP and ALP serum concentrations, which contrasts with Sahin et al (2007), who determined that ISP supplementation increased the serum concentrations of Ca and P and the activity of ALP in quail.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…In our trial, in ovo injection of different doses of ISF increased GSH-PX activity in the serum of chicks (Hajati et al, 2014;Khaligh et al, 2018). Furthermore, in vitro studies in human and pig cells challenged by hydrogen peroxide showed that ISF increased the activities and mRNA expression of SOD and GSH (Jin et al, 2015;Khaligh et al, 2018;Ma et al, 2015). In the current study, no change was observed in Ca, P, albumen, TP and ALP serum concentrations, which contrasts with Sahin et al (2007), who determined that ISP supplementation increased the serum concentrations of Ca and P and the activity of ALP in quail.…”
Section: Discussionsupporting
confidence: 51%
“…In our trial, in ovo injection of different doses of ISF increased GSH‐PX activity in the serum of chicks (Hajati et al, 2014; Khaligh et al, 2018). Furthermore, in vitro studies in human and pig cells challenged by hydrogen peroxide showed that ISF increased the activities and mRNA expression of SOD and GSH (Jin et al, 2015; Khaligh et al, 2018; Ma et al, 2015). Furthermore, Fan et al (2018) reported that GSH‐PX showed a slight increase in the liver of 21‐day‐old broilers when breeder fed DAI‐low supplemented.…”
Section: Discussionmentioning
confidence: 99%
“…These results may be attributed to the bioactive substances in soy isoflavones (i.e. phenolic compounds, daidzein, and genistein) that exert antioxidant effects (79,80) through glutathione peroxidase regulation and reduction of ROS and malondialdehyde infiltration (81) . Although several soy isoflavone doses were administered in this systematic review, subgroup analysis based on dose was not feasible due to the low number of studies.…”
Section: Discussionmentioning
confidence: 99%
“…Lately, soy isoflavone has been shown to decrease the concentrations of ROS and malondialdehyde, as well as increase the mRNA expressions and activities of superoxide dismutase and glutathione peroxidase in porcine mammary gland cells and human umbilical vein endothelial cells challenged by hydrogen peroxide [ 75 , 76 ]. These interesting findings, along with a previous report [ 45 ], indicate that isoflavones are modulators of enzymatic antioxidants (besides ROS scavengers), and that nuclear factor-erythroid 2 (Nrf2)—a key transcription factor that leads to gene transcription of various antioxidant and phase II detoxifying enzymes—is associated with this modulation [ 77 , 78 ].…”
Section: Anti-inflammatory Mechanisms Of Isoflavonesmentioning
confidence: 99%